EKSPLORASI PENERAPAN GAME BASED LEARNING TERHADAP MINAT DAN PEMAHAMAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Diasti, Ulfa Shafira Putri; Taufik, Taufik; Adi, Nur Romdlon Maslahul; Pambawati, Galuh Jevani (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to determine the effect of implementing Game-Based Learning on students’ interest and understanding in Indonesian language learning, particularly on the topic of describing plants and animals in the surrounding environment both orally and in writing. The research used a descriptive method with a qualitative approach involving Grade IIIB students at SD Islam Al-Chusnaini. Data were collected through observation and analysis of Sumatif Tengah Semester (STS) report documents. The findings show that the implementation of Game-Based Learning had a positive impact on student learning outcomes. Most students achieved scores above 85, with an average score of 91.3. The success of this method was supported by active student participation in educational games, increased learning motivation, and enjoyable learning experiences aligned with students’ learning styles. Game-Based Learning also created a more dynamic, interactive, and collaborative classroom environment, which contributed to improved student understanding of the learning material.